O papel do enfermeiro no processo educativo em saúde na educação infantil : concepções de educadores e enfermeiros - Oliveira, Pâmela Roberta de (2013)
The kindergartens’ environments are auspicious places to spread several common infectious diseases during childhood, whose incidence is worsen by age, immunity, group size, hygiene habits and degree of personal contact between children and those who provide these services in the schools. Health Education is a practice commonly developed by several institutions and professionals in their daily work, especially by the Nurse. The objective of this research is to understand the role of the Nurse in health education process in kindergarten in Barra do Garças / MT. This is a qualitative study with descriptive and exploratory aim. A recorded interview (voice recording) with semi-structured guide was used as a technique for gathering data. The study was conducted in six CMEIs, one CMEF and CMEI, two CMEFs and one EMEF. The participants were six directors, five coordinators, seven teachers of Early Childhood Education and seven nurses from Family Health Strategy Program. The following categories emerged during data analysis: the role of the nurse in the daycare / pre-school in the logic biomedical perspective; the interdisciplinary work in daycare / preschool; role of the nurse in the daycare / pre-school through pedagogy of project, the absence / presence of the nurse in the daycare / preschool; conflict of Educators with health issues; the caring for and the educating in daycare / preschool - divided or shared actions between Education and Health sectors, training for nurses, consequences of their professional performance in popular education and health and the working method of child education. The outcomes revealed a latent necessity, increasingly crescent, the integration of knowledge among educators and health professionals, not only nurses, in the fight for an education process in health which enhances the union of the caring for and the educating the children at the expense of hygienist postures and of discourses linked to the labor market. the partnerships between the Health and Education sectors are expected to be strengthen, with the active participation of the citizens in each area, in the process of decision making, related to health and life.